Symptom Presentation in Idiopathic Environmental Intolerance With Attribution to Electromagnetic Fields: Evidence for a Nocebo Effect Based on Data Re-Analyzed From Two Previous Provocation Studies - Eltiti, Stacy; Wallace, Denise; Russo, Riccardo; Fox, Elaine (Frontiers in Psychology, 2018)
Individuals with idiopathic environmental illness with attribution to electromagnetic fields (IEI-EMF) claim they experience adverse symptoms when exposed to electromagnetic fields (EMFs) from mobile telecommunication devices. However, research has consistently reported no relationship between exposure to EMFs and symptoms in IEI-EMF individuals. The current study investigated whether presence of symptoms in IEI-EMF individuals were associated with a nocebo effect. Data from two previous double-blind provocation studies were re-analyzed based on participants’ judgments as to whether or not they believed a telecommunication base station was “on” or “off”. Experiment 1 examined data in which participants were exposed to EMFs from Global System for Mobile Communication, Universal Mobile Telecommunications System, and sham base station signals. In Experiment 2, participants were exposed to EMFs from Terrestrial Trunked Radio Telecommunications System and sham base station signals. Our measures of subjective well-being indicated IEI-EMF participants consistently reported significantly lower levels of well-being, when they believed the base station was “on” compared to “off”. Interestingly, control participants also reported experiencing more symptoms and greater symptom severity when they too believed the base station was “on” compared to “off”. Thus, a nocebo effect provides a reasonable explanation for the presence of symptoms in IEI-EMF and control participants.